School drop-outs: How do their knowledge about reproductive health increase using Gendang Beleq as an Indonesian Traditional Culture? - Diarti, Maruni Wiwin; Jiwintarum, Yunan; Herawati, Lale Heny (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2020)
Background: Youth is a critical development condition and it should have understanding and awareness of sexual and reproductive health (SRH) needs. In many aspects of life, young people or adolescents who drop out of school fare worse. Those people who do not have the ability to attend school during these formative years, sadly, do not find opportunities and fall behind compared to other people who attend school. This study aimed to examine the effectiveness of Gendang Beleq as an Indonesian Traditional culture in increase the knowledge of SRH among school drops-out adolescents in Kuta coastal areas, Central Lombok, West Nusa Tenggara.Subjects and Method: This study was an experimental study using pretest-postest study without control group design. This study was conducted in Kuta coastal areas, Central Lombok, West Nusa Tenggara. A total of 30 school drops- out adolescents was selected for this study using purposive sampling. The dependent variable was SRH knowledge (fertile age, puberty, age of marriage, maturity of premarital age, and sexually transmitted infection, HIV-AIDS, and drugs). The independent variable was SRH intervention using Gendang Beleq. The data were collected using questionnaire and in-depth interview. The data were analyzed using t-test.Results: Means of SRH knowledge were increased after Gendang Beleq intervention. Fertile age (Mean= 84.58; SD= 6.58) was increased than before (Mean= 52.55; SD= 5.33), puberty was increased (Mean= 83.65; SD= 3.89) than before (Mean=52.15; SD=10.03), age of marriage was increased (Mean= 82.31; SD= 6.55) than before (Mean= 82.31; SD=5.33), maturity of premarital age was increased (Mean= 82.68; SD= 4.61) than before (Mean=57.68; SD=8.70), and sexually transmitted infection, HIV-AIDS, and drugs was increased (Mean=81.61; SD=3.11) than before (Mean=55.68; SD=8.27), and they were respectively statistically significant.Conclusion: Gendang beleq increase the knowledge regarding sexual and reproductive health among school drops-out adolescents in Kuta coastal areas, Central Lombok, West Nusa Tenggara.Keywords: Gendang beleq, knowledge, adolescents, sexual and reproductive healthCorrespondence: